Uncovering the roles of the scaffolding protein CsoS2 in mediating the assembly and shape of the α-carboxysome shell - Tianpei Li; Taiyu Chen; Ping Chang; Xingwu Ge; Vincent Chriscoli; Gregory F. Dykes; Qiang Wang; Lu-Ning Liu (mBio, 2024)
ABSTRACT Carboxysomes are proteinaceous organelles featuring icosahedral protein shells that enclose the carbon-fixing enzymes, ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco), along with carbonic anhydrase. The intrinsically disordered scaffolding protein CsoS2 plays a vital role in the construction of α-carboxysomes through bridging the shell and cargo enzymes. The N-terminal domain of CsoS2 binds Rubisco and facilitates Rubisco packaging within the α-carboxysome, whereas the C-terminal domain of CsoS2 (CsoS2-C) anchors to the shell and promotes shell assembly. However, the role of the middle region of CsoS2 (CsoS2-M) has remained elusive. Here, we conducted in-depth examinations on the function of CsoS2-M in the assembly of the α-carboxysome shell by generating a series of recombinant shell variants in the absence of cargos. Our results reveal that CsoS2-M assists CsoS2-C in the assembly of the α-carboxysome shell and plays an important role in shaping the α-carboxysome shell through enhancing the association of shell proteins on both the facet-facet interfaces and flat shell facets. Moreover, CsoS2-M is responsible for recruiting the C-terminal truncated isoform of CsoS2, CsoS2A, into α-carboxysomes, which is crucial for Rubisco encapsulation and packaging. This study not only deepens our knowledge of how the carboxysome shell is constructed and regulated but also lays the groundwork for engineering and repurposing carboxysome-based nanostructures for diverse biotechnological purposes.IMPORTANCECarboxysomes are a paradigm of organelle-like structures in cyanobacteria and many proteobacteria. These nanoscale compartments enclose Rubisco and carbonic anhydrase within an icosahedral virus-like shell to improve CO2 fixation, playing a vital role in the global carbon cycle. Understanding how the carboxysomes are formed is not only important for basic research studies but also holds promise for repurposing carboxysomes in bioengineering applications. In this study, we focuses on a specific scaffolding protein called CsoS2, which is involved in facilitating the assembly of α-type carboxysomes. By deciphering the functions of different parts of CsoS2, especially its middle region, we provide new insights into how CsoS2 drives the stepwise assembly of the carboxysome at the molecular level. This knowledge will guide the rational design and reprogramming of carboxysome nanostructures for many biotechnological applications.